Sudden large and periodic changes in heart rate in healthy young men after short periods of exercise. Issue 6349 (23rd October 1982) - Jennett, S; Lamb, J F; Travis, P
Abstract : The instantaneous heart rate and respiratory pattern were recorded immediately after brief periods of exercise in 41 healthy male students. Recordings were taken with the subjects both supine and standing. More than half of these subjects showed oscillatory heart changes when recovering supine but not when standing. During these oscillations the heart rate slowed suddenly by more than 30 beats/min; the oscillations had a period of 4 to 8 seconds, and they continued for half to two minutes. The P waves of the electrocardiogram were decreased during the slowing, consistent with increased vagal activity. When these oscillations occurred they each followed the start of an inspiration with the same latency as in respiratory sinus arrhythmia; unlike respiratory sinus arrhythmia, however, they did not occur after every inspiration but varied from 1:1 to 1:3 oscillations:breaths. They were not usually stopped by breath holding but were reduced or abolished by procedures which reduced venous return. This pattern of oscillations--"vagushalt"--seems to be different from respiratory sinus arrhythmias, and central venous pressure may contribute to the phenomenon. Although it is not widely recognised, vagushalt is probably very common and possibly its occurrence may change in disease.